1994
DOI: 10.21000/jasmr94010365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Handling of Pyritic, Acid-Forming Materials on the Chemistry of Pore Gas and Ground Water at A Reclaimed Surface Coal Mine, Clarion County, PA, USA

Abstract: A change from dragline to "selective handling" mining methods at a reclaimed surface coal mine in western Pennsylvania did not significantly affect concentrations of metals in ground water because oxidation of pyrite and dissolution of siderite were not abated. Throughout the mine, placement of pyritic material near the land surface facilitated the oxidation of pyrite, causing the consumption of oxygen (0 2) and release of acid, iron, and sulfate ions. Locally in the unsaturated zone, water sampled within or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A goal of this project was to leach calcareous rock samples under conditions likely to be encountered in coal mine spoil. The concentration of CO 2 in the atmosphere is 0.03%, whereas in mine spoil it can exceed 10% (Cravotta et al, 1994;Lusardi and Erickson, 1985). Under subsurface conditions, where CO 2 is elevated, the weathering rate of calcareous materials can be accelerated and high concentrations of alkalinity can result (e.g.…”
Section: Methods Performance Datamentioning
confidence: 99%
“…A goal of this project was to leach calcareous rock samples under conditions likely to be encountered in coal mine spoil. The concentration of CO 2 in the atmosphere is 0.03%, whereas in mine spoil it can exceed 10% (Cravotta et al, 1994;Lusardi and Erickson, 1985). Under subsurface conditions, where CO 2 is elevated, the weathering rate of calcareous materials can be accelerated and high concentrations of alkalinity can result (e.g.…”
Section: Methods Performance Datamentioning
confidence: 99%
“…A major outcome of the Phase I and II evaluations was the decision to use a controlled atmosphere, and attempt to simulate subsurface conditions in spoil piles and underground mines. Equilibrium calculations based on measured alkalinity and pH values in mine water, and field measurements show that elevated pCO 2 exist in minespoil and underground mines (Cravotta et al, 1994). .…”
Section: Total 100mentioning
confidence: 99%
“…For instance, Cravotta et al [5] reported concentrations over 16% 11 m below the surface in reclaimed coal mine spoil. However, until the early 2000s no cases of hazardous concentrations of…”
Section: Introductionmentioning
confidence: 99%
“…Soil gas sampling for isotopic studies face two challenges: (i) differences in diffusion rates of the isotopologues, 13 CO 2 and 12 CO 2 , through soil [8]; and (ii) soil transport mechanisms that drive CO 2 flow to the surface [8]. It has been shown that CO 2 from AMD-carbonate reactions accumulate at depth and only flow to the surface in episodes [4,5]. In addition, any sampling method needs to be fast and economic to cover the large tracts of land under study.…”
Section: Introductionmentioning
confidence: 99%